IDENTIFIKASI SPESIES FITOPLANKTON PENYEBAB HARMFUL ALGAL BLOOM (HAB) DI PERAIRAN TARAKAN - Weliyadi, Encik (Jurnal Harpodon Borneo, 2013)
Study on the identification of the potential Harmful Algal Bloom (HAB) species in coastal waters of Tarakan. The objectives of this study were to identify the types of potential HAB species, which cause red tide event in the coastal waters of Tarakan. Furthermore, this study was to determine the cell density of HAB species in the study area. Sampling was conducted from April to July 2012. Two sampling locations were chosen: Station 1 was located in the Port of Tengkayu 2, Tarakan and Station 2 was situated in the coastal waters of Amal. The results of the study showed that five potential HAB species were identified in Tarakan coastal waters. The species were Chaetoceros sp (class Bacillariophyceae), and four species of class Dinophyceae, which consists of Ceratium furca, Ceratium fusus, Dinophysis caudata and Protoperidinium depressum. The mean cell densities of the five HAB organisms ranged between 150-600 cells. L , 25-125 cells. L -1 . 25-150 cells. L -1 . 25-100 cells. L -1 and 25-50 cells. L -1 respectively. Chaetoceros sp dominated the area with the mean cell density of 322 ± 92 cells. L -1 compared to four other HAB species. Nevertheless, this study did not find any fish mortality events or a human illness caused by HAB species at Tarakan waters.Key word : Harmful Algal Bloom (HAB), Fitoplankton, Waters of Tarakan.